Middle to Late Pleistocene Architecture and Stratigraphy of the Lower Bengal Fan—Integrating Multichannel Seismic Data and IODP Expedition 354 Results. (13th January 2020) - Bergmann, Fenna; Schwenk, Tilmann; Spiess, Volkhard; France‐Lanord, Christian
Abstract: Utilizing a novel data set of integrated high‐resolution multichannel seismic data with IODP Expedition 354 drilling results, a Middle to Late Pleistocene stratigraphy for the lower Bengal Fan is developed. The study reveals a high lateral and temporal variability of deposition expressed by lateral shifts (often exceeding 100 km) between successive channel‐levee systems (CLSs), which occurred on average every ~15 kyr independent from sea‐level changes. The CLSs are embedded in sheeted sediments deposited out of unchannelized turbidity currents, which represent almost two thirds of the lower Bengal Fan sediments. On 100‐kyr timescales, CLSs and sheeted/unchannelized sediments build up subfans, which alternately occupied the western and the eastern Bengal Fan, while the remaining area was draped by ~10 to 20 m‐thick layers of background/hemipelagic sediments. Three subfans have been reconstructed: Subfan B (1.24–0.68 Ma) formed concurrently with the Middle Pleistocene Hemipelagic Layer, Subfan C (0.68–0.25 Ma) covered the entire study area, and Subfan D (0.25 Ma to recent) deposited concomitant with the Late Pleistocene Hemipelagic Layer. The continuous succession of subfans indicates an uninterrupted fan activity independent from sea‐level cycles at least since the Middle Pleistocene. This remarkable independent behavior in terms of sediment supply has not been observed at the Amazon Fan but is in agreement with observations from the Congo Fan. Finally, the analysis of a complete cross section through the lower Bengal Fan reveals that almost half of the sediment represents sands, indicating that the lower Bengal Fan may not generally be classified as "mud rich" (≤30% sand). Plain Language Summary: The northern Indian Ocean receives large amounts of material eroded by wind and rain onshore. Most of the sediment comes from the Himalayan mountain range and contains important information about the evolution of the Himalaya as well as the past Asian climate. After erosion, it is transported by large rivers, such as the Ganges and Brahmaputra, to the coast. Underwater, the sediment moves even farther southwards within river‐like features, the so‐called channel‐levee systems. Eventually, the material is deposited within the submarine Bengal Fan, a large sediment body covering most parts of the Bay of Bengal. In this study, we combine the results of a large underwater drilling campaign (IODP Expedition 354) with acoustic images of the subsurface from the lower Bengal Fan in order to develop a profound understanding of the timing and location of channel‐levee activity and sediment deposition. This knowledge will eventually help scientists to understand the past climate in the Himalaya region. We show that the location of sediment deposition is highly variable and can move more than 100 km laterally. These variations are investigated in detail for the last 1 million years. Key Points: Sedimentation on the Bengal Fan is strongly influenced by significant depocenter relocations on different time and spatial scales A novel stratigraphy along IODP Expedition 354 drillings reveals a sea‐level independent interplay of hemipelagic and turbiditic deposition The lower Bengal Fan has a sand content of ~44% despite its classification as a mud‐rich fan